Image-Forming Visual Basis of Empathy for Pain in Mice - Kai-Wen Geng; Rui Du; Na Wei; Chun-Li Li; Yan Wang; Wei Sun; Tao Chen; Dong-Yu Wei; Yang Yu; Ting He; Wen-Jun Luo; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2020)

A predicted protein functional network aids in novel gene mining for characteristic secondary metabolites in tea plant (Camellia sinensis) - Shihua Zhang; Yong Ma; Rui Zhang; Xiaolong He; Ying Chen; Jingke Du; Chi-tang Ho; Youhua Zhang; Guomin Han; Xiaoyi Hu (Journal of Biosciences, 2020)

Synthesis and biological evaluation of 2-phenyl-4-aminoquinolines as potential antifungal agents - Rui Yang; Wenhao Du; Huan Yuan; Tianhong Qin; Renxiao He; Yanni Ma; Haiying Du (Molecular Diversity, 2020)

CCL19 suppresses gastric cancer cell proliferation, migration, and invasion through the CCL19/CCR7/AIM2 pathway - Rui Zhou; Jun Sun; Chunping He; Chao Huang; Honggang Yu (Human Cell, 2020)

Selenium Deficiency in Chickens Induces Intestinal Mucosal Injury by Affecting the Mucosa Morphology, SIgA Secretion, and GSH-Px Activity - Xianjing He; Yucai Lin; Shuai Lian; Dongbo Sun; Donghua Guo; Jianfa Wang; Rui Wu (Biological Trace Element Research, 2020)

Surface fractal dimensions as a characterization parameter for methane adsorption–induced coal strains - Jie Zhu; Yang Zhang; Rui Zhang; Bo Zhang; Jun Tang; Fa He (Arabian Journal of Geosciences, 2020)

Design, Characterization, and Application of a pH-Triggered In Situ Gel for Ocular Delivery of Vinpocetine - Qun Ma; Rui Luo; Huimin Zhang; Manman Dai; Luyu Bai; Qingsong Fei; Fang Lei; Ning He (AAPS PharmSciTech, 2020)

BDNF improves axon transportation and rescues visual function in a rodent model of acute elevation of intraocular pressure - Rui Du; Xu Wang; Shigang He (Science China Life Sciences, 2020)

Electroacupuncture improves myocardial ischemia injury via activation of adenosine receptors - Yulan Ren; Zhihan Chen; Rui Wang; Yang Yu; Dehua Li; Yonggang He (Purinergic Signalling, 2020)
Electroacupuncture (EA) can improve myocardial ischemia (MI) injury; nevertheless, the mechanism is not entirely clear. And there were disagreements about whether the effect of EA at acupoint in disease-affected meridian is better than EA at acupoint in non-affected meridian and sham acupoint. Here, we showed that the effect of EA at Neiguan (PC6) is better than EA at Hegu (LI4) and sham acupoint in affecting RPP and ECG, increasing ATP and ADO production, decreasing AMP production, and upregulating the mRNA expression levels of A1AR, A2aAR, and A2bAR; knockdown of A1AR or A2bAR reversed the effect of EA at PC6 in alleviating MI injury; knockdown of A2aAR had no influence on the cardiac protection of EA at PC6; thus, the cardioprotective effect of EA at PC6 needs A1AR and A2bAR, instead of A2aAR; considering that the cardio protection of adenosine receptor needs activation of other adenosine receptors, one of the reasons may be that after silence of A1AR or A2bAR, EA at PC6 could not impact the expression levels of the other two adenosine receptors, and after silence of A2aAR, EA at PC6 could impact the expression levels of A1AR and A2bAR. These results suggested that EA at PC6 may be a potential and effective treatment for MI by activation of A1AR and A2bAR.

Genetic mapping and identification of new major loci for tolerance to low phosphorus stress in rice - Abdul Malik Solangi; Hira Khanzada; Ghulam Mustafa Wassan; Adnan Rasheed; Ayaz Ali Keerio; Majeeduddin Solangi; Saba Khanzada; Muhammad Faheem; Jianmin Bian; Xiaohua Pan; Rui Cai Han; Xunfeng He; et al. (Physiology and Molecular Biology of Plants, 2020)
Phosphorus (P) is one of the essential macronutrients for rice. In this study, we used 120 rice backcross recombinant inbred lines (BRILs) derived from a cross indica cv. Changhui 891 and japonica cv. 02428. To elucidate the genetic control of P deficiency tolerance in rice, we have used high quality SNPs bin markers to identify some important loci underlying phosphorus deficiency. The bin map was generated which includes 3057 bins covering distance of 1266.5 cM with an average of 0.41 cM between markers. Based on this map, 50 loci, including four novel loci, qSL - 3 , qRL - 11 , qSDW - 1 , qRDW - 1 with phenotypic variance 23.26%, 12.06%, 9.89% associated with P deficiency-related seedling traits were identified. No significant QTLs was found for root length under P+, shoot fresh weight P− and root length, shoot fresh weight for P+, P− and their ratio respectively. Root fresh weight, and root dry weight were strongly correlated to each other, and QTLs for these variables were located on the same chromosome 1 at the same region. Notably, 3 pleiotropic regions is the pioneer of our study, and these regions would facilitate map-based cloning to expedite the MAS selection for developing low phosphorous tolerant varieties. This study not only improves our knowledge about molecular processes associated with P deficiency, but also provides useful information to understand the genetic architecture of low phosphorous tolerance.

The study on loess liquefaction in China: a systematic review - Siyue He; Xiuling Wang; Haobo Fan; Hao Wang; Rui Ren; Chunxia Guo (Natural Hazards, 2020)

Technical efficiency estimation of China’s environmental protection enterprises and its heterogeneity - Ren Wang; Rui Wang; Xiaobo He (Environmental Science and Pollution Research, 2020)

Bioaccumulation of ytterbium oxide nanoparticles insinuate oxidative stress, inflammatory, and pathological lesions in ICR mice - Muhammad Adeel; Jin Tingting; Tariq Hussain; Xiao He; Muhammad Arslan Ahmad; Muhammad Kashif Irshad; Noman Shakoor; Peng Zhang; Xie Changjian; Yi Hao; Zhang Zhiyong; Rabia Javed; et al. (Environmental Science and Pollution Research, 2020)

Mechanical characteristics of soil-rock mixtures containing macropore structure based on 3D modeling technology - Yong Liu; Shao-rui Sun; Ji-hong Wei; Jing-lei Song; Yong-xiang Yu; Wei He; Ji-xing Zhang (Journal of Mountain Science, 2020)

Reconstructing the 3D digital core with a fully convolutional neural network - Qiong Li; Zheng Chen; Jian-Jun He; Si-Yu Hao; Rui Wang; Hao-Tao Yang; Hua-Jun Sun (Applied Geophysics, 2020)

A new phenanthropyran and a new biphenanthrene from the rhizomes of Dioscorea septemloba and their antioxidant activities - Tao He; Yi Liu; Rui-Feng Xiong; Xiao-Yu Li; Shou-Feng Wang; Chun-Ru Cheng (Natural Product Research, 2020)

Effects of crop straw biochars on aluminum species in soil solution as related with the growth and yield of canola (Brassica napus L.) in an acidic Ultisol under field condition - Wen-rui Zhao; Jiu-yu Li; Kai-ying Deng; Ren-yong Shi; Jun Jiang; Zhi-neng Hong; Wei Qian; Xian He; Ren-kou Xu (Environmental Science and Pollution Research, 2020)

Examining two sets of introgression lines across multiple environments reveals background-independent and stably expressed quantitative trait loci of fiber quality in cotton - Yuzhen Shi; Aiying Liu; Junwen Li; Jinfa Zhang; Shaoqi Li; Jinfeng Zhang; Liujun Ma; Rui He; Weiwu Song; Lixue Guo; Quanwei Lu; Xianghui Xiang; et al. (Theoretical and Applied Genetics, 2020)
Key message Background-independent (BI) and stably expressed (SE) quantitative trait loci (QTLs) were identified using two sets of introgression lines across multiple environments. Genetic background more greatly affected fiber quality traits than environmental factors. Sixty-one SE-QTLs, including two BI-QTLs, were novel and 48 SE-QTLs, including seven BI-QTLs, were previously reported. Abstract Cotton fiber quality traits are controlled by QTLs and are susceptible to environmental influence. Fiber quality improvement is an essential goal in cotton breeding but is hindered by limited knowledge of the genetic basis of fiber quality traits. In this study, two sets of introgression lines of Gossypium hirsutum × G. barbadense were used to dissect the QTL stability of three fiber quality traits (fiber length, strength and micronaire) across environments using 551 simple sequence repeat markers selected from our high-density genetic map. A total of 76 and 120 QTLs were detected in the CCRI36 and CCRI45 backgrounds, respectively. Nine BI-QTLs were found, and 78 (41.71%) of the detected QTLs were reported previously. Thirty-nine and 79 QTLs were SE-QTLs in at least two environments in the CCRI36 and CCRI45 backgrounds, respectively. Forty-eight SE-QTLs, including seven BI-QTLs, were confirmed in previous reports, and 61 SE-QTLs, including two BI-QTLs, were considered novel. These results indicate that genetic background more strongly impacts on fiber quality traits than environmental factors. Twenty-three clusters with BI- and/or SE-QTLs were identified, 19 of which harbored favorable alleles from G. barbadense for two or three fiber quality traits. This study is the first report using two sets of introgression lines to identify fiber quality QTLs across environments in cotton, providing insights into the effect of genetic backgrounds and environments on the QTL expression of fiber quality and important information for the genetic basis underlying fiber quality traits toward QTL cloning and molecular breeding.

SNHG16 regulates invasion and migration of bladder cancer through induction of epithelial-to-mesenchymal transition - Wenwei Chen; Tao Jiang; Houping Mao; Rui Gao; Hua Zhang; Yanfeng He; Changyi Liu; Qin Chen (Human Cell, 2020)

Neocucurbitacin D, a novel lactone-type norcucurbitacin as xanthine oxidase inhibitor from Herpetospermum pedunculosum - He-Zhong Jiang; Sha Hu; Ren-Xiang Tan; Rui Tan; Rui-Hua Jiao (Natural Product Research, 2020)

Assessment of genetic diversity in Camellia oleifera Abel. accessions using inter-simple sequence repeat (ISSR) and start codon targeted (SCoT) polymorphic markers - Pu Xiao; Huhu Liu; Dongping Wang; Wenyan Tang; Hui Yang; Chong Wang; Zhilong He; Rui Wang; Xiangnan Wang; Xiangyang Lu; Yongzhong Chen; Yun Tian (Genetic Resources and Crop Evolution, 2020)

Effects of High-Fat Diet on Steatosis, Endoplasmic Reticulum Stress and Autophagy in Liver of Tilapia (Oreochromis niloticus) - Rui Jia; Li-Ping Cao; Jin-Liang Du; Qin He; Zheng-Yan Gu; Galina Jeney; Pao Xu; Guo-Jun Yin (Frontiers in Marine Science, 2020)

Paracetamol affects the expression of detoxification- and reproduction-related genes and alters the life traits of Daphnia magna - Rui Ding; Sijia Liu; Cuiping He; Xiangping Nie (Ecotoxicology, 2020)

A salient oceanic driver for the interannual variability of wintertime haze days over the Pearl River Delta region, China - Yue Chang; Jing Wang; Zhiwei Zhu; Hua Deng; Jinhai He; Rui Lu (Theoretical and Applied Climatology, 2020)

Release of tartrate as a major carboxylate by alfalfa (Medicago sativa L.) under phosphorus deficiency and the effect of soil nitrogen supply - Honghua He; Miaomiao Wu; Lei Guo; Chenbin Fan; Zekun Zhang; Rui Su; Qi Peng; Jiayin Pang; Hans Lambers (Plant and Soil, 2020)

Plasma Endostatin Levels at Acute Phase of Ischemic Stroke Are Associated with Post-Stroke Cognitive Impairment - Sifan Qian; Ruyi Li; Chenhuan Zhang; Rui Zhang; Daoxia Guo; Xiaoqing Bu; Aili Wang; Hao Peng; Jing Chen; Yonghong Zhang; Jiang He; Tan Xu; et al. (Neurotoxicity Research, 2020)

Minor topography governing erosional distribution of SOC and temperature sensitivity of CO2 emissions: comparisons between concave and convex toposequence - Yao He; Yaxian Hu; Xin Gao; Rui Wang; Shengli Guo; Xianwen Li (Journal of Soils and Sediments, 2020)

Integration of hepatitis B virus DNA into p21-activated kinase 3 (PAK3) gene in HepG2.2.15 cells - Peng Ruan; Xiufang Dai; Jun Sun; Chunping He; Chao Huang; Rui Zhou; Isabelle Chemin (Virus Genes, 2020)

Factors Controlling Deposition of Metallic Minerals in the Meng’entaolegai Ag-Pb-Zn Deposit, Inner Mongolia, China: Evidence from Fluid Inclusions, Isotope Systematics, and Thermodynamic Model - He Yang; Wanli Ma; Rui Wang; Xueli Ma; Keyong Wang (Journal of Earth Science, 2020)

Responses of Alpine Wetlands to Climate Changes on the Qinghai-Tibetan Plateau Based on Remote Sensing - Rui Wang; Min He; Zhenguo Niu (Chinese Geographical Science, 2020)

Systematic Identification and Comparative Analysis of Human Cartilage-Derived Self-peptides Presented Differently by Ankylosing Spondylitis (AS)-Associated HLA-B*27:05 and Non-AS-associated HLA-B*27:09 - Chang Ge; Wenzhi Zhang; Rui He; Haiping Cai (International Journal of Peptide Research and Therapeutics, 2020)

The stability and pressure behavior characteristics of a special L-type face end formed by low-pressure mining technology without pre-driving roadway - Ya-jun Wang; Jun Yang; Man-chao He; Rui-feng Huang; Xi-chun Tian; Jian-ning Liu; Hao-jie Xue (Arabian Journal of Geosciences, 2020)

Extraction of P- and S-wave angle-domain common-image gathers based on first-order velocity-dilatation-rotation equations - Kai-Rui Li; Bing-Shout He (Applied Geophysics, 2020)

Decreasing intraocular pressure significantly improves retinal vessel density, cytoarchitecture and visual function in rodent oxygen induced retinopathy - Rui Du; Xu Wang; Ke Shen; Shigang He (Science China Life Sciences, 2020)

MiR-125a-5p Regulates Vitamin D Receptor Expression in a Mouse Model of Experimental Autoimmune Encephalomyelitis - Han-Chun Long; Rui Wu; Chun-Feng Liu; Fei-Long Xiong; Zu Xu; Dian He; Yi-Fan Zhang; Bing Shao; Ping-An Zhang; Guang-Yin Xu; Lan Chu (Neuroscience Bulletin, 2020)

Application of metagenomic next-generation sequencing for bronchoalveolar lavage diagnostics in critically ill patients - Ying Li; Bing Sun; Xiao Tang; Ya-lan Liu; Hang-yong He; Xu-yan Li; Rui Wang; Fei Guo; Zhao-hui Tong (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Crystal structure of impurity-free rhodochrosite (MnCO3) and thermal expansion properties - Wen Liang; Lin Li; Rui Li; Yuan Yin; Zeming Li; Xiqiang Liu; Shuangmin Shan; Yu He; Yong Meng; Zengsheng Li; Heping Li (Physics and Chemistry of Minerals, 2020)

Isolation, identification and character analysis of Streptococcus dysgalactiae from Megalobrama terminalis - Fei Zhao; Shan He; Ai‐ping Tan; Xue‐zhong Guo; Lan Jiang; Cui Liu‐Fu; Yu‐ting Deng; Rui‐quan Zhang (Journal of Fish Diseases, 2020)
Pure bacterial cultures were isolated from different tissues of moribund Megalobrama terminalis from a high mortality event that occurred at a farm in Foshan, China. Two isolates (F2 and F3) were identified as Streptococcus dysgalactiae subsp. dysgalactiae based on morphological and biochemical detection as well as molecular analysis. In brain heart infusion broth, the best growth conditions of isolate F3 were 35ºC, salinity 5‰ and pH 7. Furthermore, infection with isolate F3 (1.2 × 10 6 CFU/fish) led to the death of M. terminalis and zebrafish ( Danio rerio ). However, isolate F3 had no obvious pathogenicity to tilapia (GIFT, Oreochromis niloticus ). When the water temperature was 29ºC, the corresponding mortality rates for zebrafish infected by isolate F3 were higher than those at 23ºC. Culture for 24 and 72 hr with isolate F3 resulted in the same mortality rates for zebrafish. The antimicrobial susceptibility assay revealed that isolate F3 was susceptible to ampicillin, florfenicol and several other antibiotics but resistant to nalidixic acid, streptomycin, sulfamethoxazole/trimethoprim, neomycin and amikacin. To our knowledge, this is the first report that S. dysgalactiae infected the subtropical freshwater fish M. terminalis , which indicates that this bacterium is a potential threat to subtropical freshwater fish.

A Bayesian approach to seismic inversion based on GASA algorithm - Rui-qing Hu; Yan-chun Wang; Yang Gao; Shao-he Cao; Zhan-wei Yue; Qi Wang (Arabian Journal of Geosciences, 2020)